Predictive modeling of asthma drug properties using machine learning and topological indices in a MATLAB based QSPR study - Bayati, Jalal Hatem Hussein; Mahboob, Abid; Amin, Laiba; Rasheed, Muhammad Waheed; Alameri, Abdu (Springer Nature, 2025)
Machine learning is a vital tool in advancing drug development by accurately predicting the physical, chemical, and biological properties of various compounds. This study utilizes MATLAB program-based algorithms to calculate topological indices and machine learning algorithms to explore their ability to predict the physio-chemical properties of asthma drugs. By combining machine learning with topological indices, we can conduct faster and more precise analyses of drug structures. As we deepen our understanding of the relationship between molecular structure and performance, the integration of machine learning with QSPR research highlights the significant potential of computational strategies in pharmaceutical discovery. The use of machine learning algorithms such as random forest and extreme gradient boosting is essential in this process. These algorithms leverage labeled data to predict complex molecular processes, aiding in the discovery of new medication options and enhancing their properties. These methods enhance the accuracy of physical and chemical property predictions, streamline the drug discovery process, and efficiently evaluate large datasets through machine learning. Ultimately, these advancements facilitate the development of innovative and effective treatments.